Fate of glyphosate residue in the soil and water system of an oil palm plantation - Othman, Nurfaradilla (2013)
The herbicide glyphosate is widely used in oil palm plantations for the control of a wide range of broadleaf weeds, woody plants and grasses, to ease the collection of palm fruits and to ensure the safety of workers against wild animals hiding among the tall weeds. Currently, lifecycle assessment of environmental impacts is a requirement particularly for exported products such as palm oil and there is insufficient documented data on the residue of glyphosate in the oil palm ecosystem to support the lifecycle assessment. Adsorption and degradation are the most important factors that affect the fate of pesticides in the soil and consequently determine their distributions in the soil/water environment. Thus, this project was carried out to determine the behaviour and possible residues of glyphosate in soil and water of oil palm ecosystem through three specific objectives: 1) to investigate the adsorption and desorption of glyphosate in different soils under oil palm cultivation, 2) to determine the half-life of glyphosate in soils under oil palm cultivation and 3) to determine the residues of glyphosate in the soil and water of oil palm plantation. The first objective was achieved when adsorption and desorption study was conducted on four mineral soils, Inceptisol (Selangor soil), Inceptisol (Briah Soil) and Ultisol (Serdang and Rengam soils) and Histosol (a peat soil) collected under oil palm plantation from 0 - 15 cm and 15 - 30 cm depths using batch equilibrium technique. The concentrations of glyphosate used were 0, 20, 40, 60, 80, 100, and 120 μg/mL. The adsorption and desorption isotherms were fitted to the linear and Freundlich equations. Adsorption of glyphosate was in the following decreasing order: Selangor > Briah > Rengam > Serdang > peat with the highest adsorption being 85.5 L kg -1. The results indicated that adsorption of glyhosate was positively correlated with soil oxides and clay content. The high adsorption of the Selangor soil was expected and can be explained by the high soil oxides and clay content in the soil series compared to the other soil series. In contrast, desorption of glyphosate was in the following order: Rengam > Serdang > Peat > Selangor > Briah. This result revealed that adsorption capacity of glyphosate was strongly correlated with soil oxides and clay content. The second objective was achieved through a degradation study in the laboratory using incubation technique. The effect of microbial activity on glyphosate was studied in a Selangor soil collected at 0 - 15 cm depth. The sterilized and non-sterilized soils and both were treated with either a 100% recommended field dosage (41 g.a.i/ha) of glyphosate and 200% recommended dosage. Each soil treatment was done in triplicates. Samples were analyzed at 0, 3, 7, 21, 42, 60, 100, 120 and 140 days after treatment. Degradation rates of glyphosate in Selangor soil (sterilized and nonsterilized) follow the first order kinetics. For non-sterilized soil, the residue of glyphosate can be detected until 35 days after the incubation period for single recommended field dosage and for double recommended dosage the residue can be detected until 60 days after incubation. Whereas, for sterilized soil, the degradation of glyphosate in the recommended field dosage is detected until 80 days and for double recommended dosage is detected until 120 days after the incubation period. The half-life (t1/2) of glyphosate in sterilized soil for double recommended field dosage was 4 and 8.3 days for recommended field dosage. The half-life (t1/2) of glyphosate in non- sterilized soil for double recommended field dosage is 17.7 and for recommended field dosage is 12.2 days. From the results obtained, we can see that sterilized soil gave the longer t1/2 compared to non-sterilized soil in Selangor soil 5% level of significance. A field experiment was carried out at Ladang Telok Datok, Banting. The type of soil at this site was clay soil and the series was Selangor (Typic Tropaquept). The study plots were conducted in Completely Randomized Design (CRD). The study was conducted at two different seasons, the wet and dry season. In this study, glyphosate was applied at a recommended and double recommended field dosage. During the wet season, glyphosate was not detected at all in the soil and water which indicates that glyphosate was washed away or the soil and water did not contain glyphosate in detectable quantities. On the other hand, for the dry season, residue of glyphosate on the topsoil (0 – 15 cm) was detected until day 7 and 35 for recommended and double recommended dosage, respectively. Whereas, residue of glyphosate on the subsoil (15 – 30 cm) was detected until day 1 and 3, for recommended and double recommended dosage, respectively. However, the level is below the threshold level of 6 μg/L which is considered harmful for soil flora and fauna. The higher concentration of glyphosate applied will cause its residue to stay longer in the soil. Glyphosate residue was not detected in soil below 30 – 45 cm in each single and double recommended field dosage. The residues in water collected from PVC tube installed in the field and sub stream were not detected for both dosages. All results showed that glyphosate adsorption in soil were significantly influenced by clay content, type of clay and soil oxides. Glyphosate detected in the soil up to 35 days. However, the glyphosate residue was not detectable in groundwater even though with stimulated double recommended dosage. Glyphosate residue has a short half-life (8 days) in the soil and could be considered as essentially non-leachable to the groundwater and safe for the environment.